Removal of natural organic matter in waters using hydrodynamic cavitation and hydrogen peroxide (HC-H2O2) - Araujo, Matheus Neves de; Soeira, Thiago Vinicius Ribeiro; Poleto, Cristiano; Rezende, Elias Gabriel Fernandes de; Cappa, Otávio Augusto Puglieri; Ferreira, Deusmaque Carneiro; Rocha, Vinícius Carvalho; Gonçalves, Julio s Cesar de Souza Inácio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The presence of natural organic matter (NOM) in water does not present direct risk to the human body or to the environment. However, its presence along with other pollutants can lead to countless issues and damage human health and the environment. The hydrodynamic cavitation (HC) phenomenon started being used in the early 21st century as a process capable of treating supply-water and wastewater based on pollutant and pathogen degradation. Process effectiveness increases when it is combined to chemical agents, creating an advanced oxidation process (AOP). Although several studies have presented broaden applications for the HC process, its use for NOM removal from supply-water was not yet assessed; therefore, it remains a gap in scientific knowledge. The aim of the current study is to assess HC potential in NOM removal. In order to do so, the experiments were carried out in bench scale hydrodynamic cavitation system operated at batch model within 15-min duration period-of-time. In addition, decantation experiments (24-h period-of-time) were performed in order to check HC influence on molecules found in reaction medium after the exposure of NOM to the phenomenon. NOM was produced by a synthetic humic acid (HA) matrix at fixed concentration of 100 ppm. In total, 16 experiments were carried out; each experiment was featured by the following pair: pH (2.6, 3.0, 3.5 and 5.5) and hydrogen peroxide (0, 1, 5 and 30 mL). The best removal efficiencies (34%-36%) were observed in the most acidic pH ranges (2.6-3.0) at H2O2 concentration of 15mL. Results have presented high NOM removal efficiency (approximately 90%) after decantation at the most acidic pH ranges, as well. It can be explained by the fact that hydrodynamic cavitation in acid solution can break molecular structures suspended in the liquid medium, which favors decantation. Based on the present study, hydrodynamic cavitation with hydrogen peroxide addition can remove NOM from water; moreover, pH control is an essential factor for process development.